Studi Laju Sedimentasi di Muara Sungai Perancak Menggunakan Pemodelan Numerik - Pandu Pratama Putra; I Wayan Arthana; I Gede Hendrawan (Journal of Marine Research and Technology, 2023)
Perancak is an estuary area with land use in mangroves and ponds. Land changes that have occurred at the Perancak River estuary and tidal flooding in recent years have increased the potential for sedimentation problems that can cause silting of the riverbed. This study aims to determine the sedimentation rate and identify the potential for siltation in the estuary of the Perancak River. Sediment modeling uses the Finite Volume Coastal Ocean Model (FVCOM) by entering primary and secondary data such as bathymetry, tides, temperature, salinity, river discharge, sediment type, and Total Suspended Solid (TSS) concentration. Modeling for 33 days (January - February 2022). The results showed that the sedimentation rate in the Perancak River estuary ranged from 0.25 to 18.8 kg/m2/day, with an average of 3.83 kg/m2/day. Sedimentation rates are high in the estuary areas and riverbanks bordering the mainland. The potential for siltation shows that it occurs at river mouths with a silting value of about 0.01 m/year to more than 0.05 m/year.